Accounting Competition Vol. 2.0 sebagai Wadah Optimalisasi Kreativitas Generasi Muda terhadap Perkembangan Akuntansi - Murapi, Ikang; Oki Astarini, Dewa Ayu; Sriwinarti, Ni Ketut; Septian, Defel; Khairunnisa (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
The Accounting Competition program is a form of community service which is an annual routine agenda carried out by lecturers and students of the Bumigora University accounting study program. In the second year of implementation, this activity was named ACTION VOL 2.0 at SMA/SMK/MA level throughout Lombok Island with the theme "Let's Build Your Career Plan and Prove Your Accounting Passion With The Right Actions". The aim of this activity is to attract the interest of SMA/SMK/MA female students to further improve their abilities and can be used as a benchmark for the extent of the participants' understanding and knowledge in the field of accounting in order to deal with related issues in the current era of digitalization which have an impact on global competition. Therefore, it is hoped that this Accounting Competition will be able to become a means of increasing students' interest, talent and creativity in preparing themselves for college or the world of work, especially in the field of accounting. Implementation methods used: lectures to convey material concepts, practice completing one accounting cycle in the form of cases, and providing guidance. The results of monitoring and evaluation showed that the participants were able to absorb more than 60% of the training activity program material provided. The participants also felt satisfied and considered that the Accounting Competition activity was important and useful. The results of guidance in the field show that the majority of SMA/SMK/MA students on the island of Lombok already have an understanding of preparing financial reports based on accounting principles with the guidance of a team of lecturers from the Bumigora University accounting study program.